Manajemen Pembiayaan Modal Kerja Murabahah pada Bank Syariah Indonesia - Ami'in, Siti Nur; Yuhrotun, Yuhrotun; Dimyati, Ahmad (JIOSE: Journal of Indonesian Sharia Economics, 2022)
This study aims to determine the management of the implementation of murabahah Working Capital Financing (PMK) at Bank Syari'ah Indonesia KCP 2 Pati and evaluate Murabahah Working Capital Financing (PMK) at Bank Syari'ah Indonesia KCP 2 Pati in 2021. To find out the implementation management and evaluate the Murabaha Working Capital Financing (PMK) in 2021 in depth and comprehensively, this study uses descriptive qualitative research methods based on interviews and documentation. The results showed that the management of the implementation of Working Capital Financing (PMK) at Bank Syari'ah Indonesia KCP 2 Pati was based on the POAC management function, its duties and authorities had been carried out in accordance with the SOPs at Bank Syari'ah Indonesia KCP 2 Pati. Furthermore, the results of the evaluation of Murabahah Working Capital Financing (PMK) in 2021 at Bank Syari'ah Indonesia KCP 2 Pati, namely an increase in financing income, this is evidenced by the results of data explaining that the realization of Working Capital Financing (PMK) was successfully achieved in 2020, which is 14,845,000,000. While the realization that has been achieved in 2021, which can reach 25,608,000,000 with this, Bank Syari'ah Indonesia KCP 2 Pati must continue to maintain the development of Murabahah Working Capital Financing (PMK) that has been obtained. So that by continuing to increase the existing Murabahah Working Capital Financing (PMK), it can have a good impact on Bank Syari'ah Indonesia KCP 2 Pati.